2004
DOI: 10.1016/s1054-139x(04)00088-6
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of hopefulness for adolescents

Abstract: The findings of this study demonstrate that hopefulness is a coping strategy used by female adolescents, both healthy and ill, that is closely related to their perceived sense of self-esteem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
10
0
6
Order By: Relevance
“…Self-esteem is an essential component of an ego-identity which is the cornerstone of successful adolescent psychosocial development and self-care (Cantrell & Lupinacci, 2004). High self-esteem had been shown to be associated with better mental health C N C N C N C N and delinquency was explored by Donnellan, Trzesniewski, Robins, Moffi tt, and Caspi (2005).…”
Section: Introductionmentioning
confidence: 99%
“…Self-esteem is an essential component of an ego-identity which is the cornerstone of successful adolescent psychosocial development and self-care (Cantrell & Lupinacci, 2004). High self-esteem had been shown to be associated with better mental health C N C N C N C N and delinquency was explored by Donnellan, Trzesniewski, Robins, Moffi tt, and Caspi (2005).…”
Section: Introductionmentioning
confidence: 99%
“…3 Intriguingly, Cantrell and Lupinacci found that cancer patients had higher levels of hopefulness than normal controls and that selfesteem and hopefulness were more highly correlated in girls than in boys. 4 In a study by Zebrack and Chesler objective factors like physical after-effects or relapse had significant effects on adolescent self-image and life outlook. 5 Age was found to affect psychological responses in Swedish child and adolescent cancer patients; preadolescents worried most about death, while young adolescents worried more about physical appearance.…”
mentioning
confidence: 99%
“…Literatür incelendiğinde, umutsuzluk ve depresyon arasında pozitif doğrusal bir ilişki olduğu görülmektedir. 42,43 Umutsuzluk, depresyonun bir parçası ve merkezi olarak kabul edilmektedir. Depresyonun temelinde en fazla umutsuzluk duyguları yer almaktadır.…”
unclassified
“…Depresyonun temelinde en fazla umutsuzluk duyguları yer almaktadır. 30,31,43 Umutsuzluk, hızlı değişimlerin yaşandığı adolesan dö-neminde, bireyin tedavi nedeni ile onu birçok açıdan savunmasız bırakan kanser gibi ölümcül bir hastalıkla baş etmesini olumsuz etkilemektedir. [42][43][44] Bunun sonucunda, kontrol edilemeyen umutsuzluk ve çaresizlik duyguları ve yaşamın değersizleştiği hissi depresyona yol açmaktadır.…”
unclassified
See 1 more Smart Citation